Acquisition of Knowledge From Customers as an Element Increasing the Success of New Products - Frąckiewicz, Ewa (Advanced Information Technologies for Management – AITM 2008, 2008)
Businesses operate in an uncertain and complex environment. Products age very quickly, they are replaced with new offers, which are better adapted to consumer reąuirements, and the likes and affordability of customers also change all the time. Therefore, it is necessary to conduct the never-ending research of customer opinions, attitudes and preferences. This new optics is based on the exploration and active role of the customer in the new product creation process.The article emphasizes the necessity of change in the attitude towards collecting the information about customers into collecting the information from, about and for customers (Customer Knowledge Managenet concept) and same limitations of this idea.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 79-85